2018
DOI: 10.31332/zjpi.v4i2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Islam Dan Kebhinekaan di Indonesia: Peran Agama Dalam Merawat Perbedaan

Abstract: Differences and diversity are a necessity, they cannot be avoided in human life. Differences arise from various aspects, such as differences in ethnicity, race, nation and religion. In the Indonesian context, this difference can be seen from the formation of the Indonesian state, where the Indonesian population consists of various tribes, races, and religions, so that disputes often occur between tribes, or between religious follower. Through this study, the author focuses his research on the role of Islam and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
0
14
0
12
Order By: Relevance
“…Indeed, in the concept of diversity, the values of Indonesian Unity have succeeded in uniting various tribes spread across the archipelago (Anwar, 2018). In a pluralistic Indonesian society, there are two terms that are important to understand, namely plurality (plurality) and diversity (heterogeneity).…”
Section: Fostering the Value Of Indonesian Unitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the concept of diversity, the values of Indonesian Unity have succeeded in uniting various tribes spread across the archipelago (Anwar, 2018). In a pluralistic Indonesian society, there are two terms that are important to understand, namely plurality (plurality) and diversity (heterogeneity).…”
Section: Fostering the Value Of Indonesian Unitymentioning
confidence: 99%
“…differences are forced to merge into one understanding that is built by certain groups. (Anwar, 2018) The values of Indonesian Unity that have been built by these nationalist religious figures need to get serious attention for all citizens throughout the archipelago by using all sources existing resources, to eliminate misinterpretations of the existence of Indonesia, in a total, directed and integrated manner.…”
Section: Fostering the Value Of Indonesian Unitymentioning
confidence: 99%
“…Meanwhile Hartoyo (2010) in his research concluded that openness to others is an important requirement to capture ethnocentrism. Furthermore, Anwar (2018) states that from an Islamic point of view, difference is a nature, which is then implemented by Indonesian Muslims in the life of the nation and as a homeland. Lestari (2015) provides an overview of the results of his research that a study of cultural diversity not only provides a comprehensive picture but more than that, can foster a dialogue of perceptions of racial harmony in the midst of national life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…18 Stigma negatif terhadap Islam muncul karena perilaku dan sikap beberapa orang dan kelompok muslim garis keras yang mengaku sebagai Islam sejati tetapi anti kebhinekaan dan anti Pancasila. 19 Label negatif ini didukung oleh laporan tindakan intoleransi yang dilakukan oleh beberapa kelompok umat Islam dan tokoh-tokoh Islam radikal seperti ujaran kebencian yang dilakukan Habib Rizieq Shihab atau Ustadz Yahya Waloni. 20 Padahal agama pada hakikatnya adalah kasih dan sumber perdamaian.…”
Section: Gereja DI Tengah Kebinekaan Bangsa Indonesiaunclassified